Enhancing Helminthiasis Prevention and Health Literacy among children through Pharmacist Engagement in the Sidomulyo Health Center Area: Peran Apoteker dalam Meningkatkan Kesadaran dan Pencegahan Cacingan pada Anak di Wilayah Kerja Puskesmas Sidomulyo - Idris, Viviana (Jurnal Abdita Naturafarm, 2025)
The deworming program conducted by pharmacists in the working area of Sidomulyo Public Health Center in 2024 represents a strategic public health intervention aimed at reducing the burden of soil-transmitted helminth infections among children aged 1 to 12 years. Implemented across five urban villages and involving 26 educational institutions—including Posyandu, early childhood centers, and elementary schools—the program successfully reached 100% coverage, administering treatment to all 5,167 targeted children. Pharmacists played a central role throughout the initiative, not only ensuring accurate dosing and safe drug administration but also delivering health education, monitoring for adverse effects, and maintaining detailed records. Their direct involvement enhanced the quality and accountability of the intervention, while also fostering greater awareness of hygiene and preventive practices among students, teachers, and caregivers. Aligned with Indonesia’s Ministry of Health Regulation No. 15 of 2017 on helminthiasis control, this initiative contributes meaningfully to national goals for neglected tropical diseases (NTDs) elimination, improved child nutrition, and the strengthening of primary healthcare services. The program’s integrated, school-based approach—anchored by pharmaceutical expertise—offers a replicable model for other regions seeking to advance child health outcomes through community-centered, multisectoral collaboration.